HUBUNGAN ANTARA KOHESIVITAS DENGAN INTENSI PERILAKU AGRESI PADA SUPORTER SEPAK BOLA - Anfa Safitri; Sonny Andrianto (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2015)
This research aims to find out there is whether or not a corelation between cohesivity with intention of aggression behavior on football supporters. Early allegations put forward in the present study is there is a positive corelation between cohesiveness with Intention of aggression behaviour. The subjects in this research is 50 student Supporters of football Slemania, everything is made up of men. The scale is a scale used Intention of aggression behaviour laid out based on intention behavior researchers according to the aspect Fishbein dan Ajzen (1975) he General behavior of aggression according to classification Buss & Perry (Nashori & Diana, 2007), as for measuring cohesiveness using aspects of forsyth (1999).Methods of data analysis conducted in the present study uses statistical analysis using correlation spearmant correlation coefficients of r = 0,265 show with p = 0, 014 (p<0,05). Correlation analysis can be taken to mean that there is a very significant positive relationship between cohesiveness with Intention of aggression behaviour on football supporters. That means the higher the level of cohesiveness owned by supporters then it will be the higher Intention of aggression behaviour. Conversely, the lower the level of cohesiveness that it will be the lower clubs too Intention of aggression behaviour.